Strategi Komunikasi dalam Pembinaan Tahfidz di Pondok Pesantren Tahfidz Al-Quran Ath-Thabraniyah - Muslihatun Amaliah; Ilah Holilah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to examine the communication strategies implemented in the Qur’an memorization (tahfidz) program at Al-Qur’an Ath-Thabraniyah Islamic Boarding School (Pesantren). The tahfidz program is a complex process that not only emphasizes the cognitive aspect of memorization but also involves deep emotional and spiritual approaches. Communication strategies serve as the main instrument in building understanding, creating acceptance, and motivating students (santri) to achieve their memorization targets. This research uses a qualitative approach with methods including observation, interviews, and documentation to obtain in-depth data. The findings reveal that tahfidz instructors apply communication strategies based on Pace and Faules’ theory, which consists of three main objectives: To Secure Understanding, To Establish Acceptance, and To Motivate Action. These strategies are applied through providing insight into the virtues of Qur’an memorizers, setting appropriate schedules for memorization activities, and delivering motivation through inspirational stories and the benefits of memorizing the Qur’an. The tasmi’ sessions, held regularly, also serve as a medium for evaluation and for strengthening the students’ spiritual and mental development. With effective communication strategies, the tahfidz guidance process becomes more efficient, thus enhancing students’ enthusiasm and discipline in memorizing the Qur’an optimally.